The Motivation of need the Code of Law Department the Territorial Command of Interior Troops, Ministry of Internal Affairs, Ukraine - Shmakov, О. М. (Honor and Law, 2019)
Offers the change to Code of Law Department the Territorial Command of Interior Troops, Ministry of Internal Affairs, Ukraine (general provisions, primary duty, function, organization of activity management Territorial Command when performing the operative problems and decision of the administrative questions) represented.